English Language in the Educational Enterprise of British India - Gairanlu, Pamei (JOURNAL OF INDIAN EDUCATION, 2016)
English in India was and still is “the Command of Language and the Language of Command” (Cohn, 1996). During the British rule, English education was designed as a mass project to train Indians for the service of their Colonial masters. The Minute on Education (Macaulay, 1835) was a harbinger of the colonising of the minds, language and identity through institutionalised system of schooling and higher learning. In the guise of a benevolent provision, knowledge dissemination became a strategy of control. Collective mission of translating and interpreting texts of Indians into the language of the Master and vice-versa was initiated. It facilitated the effective accomplishment of English as the qualifier of the erudite and the elite. This became a goal to be pursued by the masses. English education in British India was not merely an educational enterprise but an existential exercise, which left indelible imprints on the psyche of the people.